The Unique Interaction Behavior Between a Superconductor Coil and a Magnet: A Comprehensive Review - Xin, Ying; Li, Wenxin; Yang, Tianhui (Journal of Electronics and Electrical Engineering, 2025)
It was found that the interaction between a superconductor coil and a magnet does not comply with one of the primary interpretations of Lenz’s law: `the current induced in a circuit due to a change or a motion in a magnetic field is directed so as to exert a mechanical force opposing the motion’. There are a number of exclusive features characterizing the interaction between a superconducting coil and a magnet. The discovery of this unique behavioural interaction leads to a principle for developing a new kind of superconducting energy conversion/storage device. With a high-temperature superconducting (HTS) coil and a magnet, this new device is able to complete an energy conversion cycle from mechanical to electromagnetic and then back to mechanical without the need for either a power supply or a motor/generator. Inherently, this kind of device has a simple structure, high energy conversion efficiency, high energy storage density, and low operational energy loss. The optimization of the configuration of the superconductor coil and magnets to enhance the storage capacity and conversion efficiency has been investigated and validated through theoretical analysis, numerical modelling and experimentation. This article systematically reviews the discovery, the working principle and state of the art of the new energy converter/storage device as well as its application potentials.